Stress resultant intensity factors evaluation of cracked folded structures by 6DOFs flat shell meshfree modeling. (November 2019) - Tanaka, S.; Dai, M.J.; Sadamoto, S.; Yu, T.T.; Bui, T.Q.
Abstract: Several numerical examples for cracked folded structures are analyzed to investigate the mixed-mode stress resultant intensity factors (SRIFs). The kinematic formulations of structures are derived by the first order shear deformation plate theory. A Galerkin meshfree six degrees of freedom (6DOFs) flat shell is employed, in which the reproducing kernel (RK) is used as the meshfree interpolant. A diffraction method, visibility criterion and enriched basis are introduced to model the through crack. J-integral is evaluated based on the stress resultants and is decomposed into the symmetric and asymmetric parts for extracting the mixed-mode SRIFs. Not only the stiffness matrix but also the J-integral are discretized by nodes. They are numerically integrated by the stabilized conforming nodal integration (SCNI) and the sub-domain stabilized conforming integration (SSCI) techniques. The effectiveness of the meshfree modeling and accuracy in the SRIFs are discussed. Highlights: Cracked folded structures are analyzed using meshfree method. SCNI/SSCI are used in the crack modeling based on RKPM meshfree method. High accuracy SRIFs and path-independency are obtained.